2017
DOI: 10.3390/molecules22050714
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Oxidative Stress and Antioxidant Defense in Romanian Patients with Type 2 Diabetes Mellitus and Obesity

Abstract: Type 2 diabetes mellitus (T2DM) is strongly associated with obesity. The adipose tissue secretes bioactive adipokines leading to low grade inflammation, amplified by oxidative stress, which promotes the formation of advanced glycation end products and eventually leads to dyslipidemia and vascular complications. The aim of this study was to correlate anthropometric, biochemical and oxidative stress parameters in newly diagnosed (ND) T2DM patients and to investigate the role of oxidative stress in T2DM associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 58 publications
(50 reference statements)
8
48
0
2
Order By: Relevance
“…Similar findings of increased oxidant parameters and a decrease in antioxidants in patients with MetS have been reported in previous studies (19)(20)(21). However, there is a lack of information on the interaction between MetS and aging over the OxS status among elderly women.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar findings of increased oxidant parameters and a decrease in antioxidants in patients with MetS have been reported in previous studies (19)(20)(21). However, there is a lack of information on the interaction between MetS and aging over the OxS status among elderly women.…”
Section: Discussionsupporting
confidence: 78%
“…However, there is a lack of information on the interaction between MetS and aging over the OxS status among elderly women. Previous studies in this area were predominantly conducted on individuals with multi-metabolic disorders (such as diabetes, hypertension, or hyperlipidemia) (8,14,16,20). By contrast, our study population sample had no metabolic or specific established diseases.…”
Section: Discussionmentioning
confidence: 61%
“…Adiponectin level of K(-) in the end of study (11.9 mg/L) was considered as normal although it decreased 1.5%. Normal adiponectin level in normal subject is 7-12 mg/L [36]. Decreasing of adiponectin level in the end of study was postulated the standard diet laboratory Comfeed II containing low antioxidant that led adiponectin level decrease.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by several reports on various risk factors of MetS, but none of them have organized the MetS on the basis of severity as assessed by z-score. Ravi Kiran et al [28] found a lower TAC in diabetic and MetS respondents, Picu et al [29], found low TAS along with low antioxidant enzymes, suggesting a strong association between T2DM and obesity, insulin resistance and OS, Bakhtiyari et al [30] reported a far greater effect of MetS than age on OS in senior women, as indicated by a strong correlation of high TG and low HDL-C, with MDA and TAC. Hopps et al [31] found significantly lower TAS in MetS non-diabetics but not in diabetic MetS respondents, and like us, they concluded that the evaluation of TAS may be a useful marker in the monitoring of MetS.…”
Section: Groupsmentioning
confidence: 99%